2009
DOI: 10.1371/journal.pone.0005709
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat Co-Operates with IFN-γ and TNF-α to Increase CXCL10 in Human Astrocytes

Abstract: HIV-associated neurological disorders (HAND) are estimated to affect 60% of the HIV infected population. HIV-encephalitis (HIVE), the pathological correlate of the most severe form of HAND is often characterized by glial activation, cytokine/chemokine dysregulation, and neuronal damage and loss. However, the severity of HIVE correlates better with glial activation rather than viral load. One of the characteristic features of HIVE is the increased amount of the neurotoxic chemokine, CXCL10. This chemokine can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 69 publications
4
38
0
Order By: Relevance
“…43 Interestingly, p38 MAPK has also been implicated in the production and release of IP10 in astrocytes exposed to HIV-1 and Tat. [44][45][46] In addition, HIV-1 and Tat were reported to activate p38 MAPK in infected or stimulated neurotoxic monocytes and MDM. 47 Furthermore, p38 MAPK activation in iDC appears to be critical to the role played by these cells in the differentiation of Th17 helper T cells, which are preferentially targeted by HIV and ultimately are severely depleted, especially in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…43 Interestingly, p38 MAPK has also been implicated in the production and release of IP10 in astrocytes exposed to HIV-1 and Tat. [44][45][46] In addition, HIV-1 and Tat were reported to activate p38 MAPK in infected or stimulated neurotoxic monocytes and MDM. 47 Furthermore, p38 MAPK activation in iDC appears to be critical to the role played by these cells in the differentiation of Th17 helper T cells, which are preferentially targeted by HIV and ultimately are severely depleted, especially in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Acutely, increased IL-1β and TNFα is reported to be a direct result of astrogliosis and microgliosis, ie., activated glial cells. For example, IL-1β induces expression of intercellular adhesion molecule-1 (ICAM-1) and TNFα alpha induces chemokine CXCL 10 and MCP-1 (monocyte chemo-attractant protein-1, also known as CCL2 and type I inflammatory monocyte), that both contributes to astrocytic activation (Ballestas et al, 1995; Gao et al, 2010; William, et al, 2009). Thus, proinflammatory cytokines are directly involved in persistent glial activation in both the acute (less than few days) and the chronic (more than 4 weeks) phases of injury via cell adhesion molecules, chemokines and chemoattractants for infiltrating immune cells.…”
Section: Glial Activation Mechanisms Following Scimentioning
confidence: 99%
“…Tat has indeed been detected in and secreted by astrocytes that are latently infected with HIV (9,25). Tat alters astrocyte growth (21,22,26) and induces expression of cytokines and chemokines in astrocytes such as MCP-1, IL-1␤, IL-6, RANTES, and CXCL10 (17,27,28), which could in turn recruit more macrophages/ monocytes and lymphocytes into the CNS (13)(14)(15)(16). Studies, including ours, have shown that astrocytes potentiate Tat neurotoxicity (16,20,22), probably through Tat-mediated transcriptional activation of glial fibrillary acidic protein (GFAP) expression (29 -31).…”
mentioning
confidence: 99%